2017
DOI: 10.1002/pbc.26744
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low bone mass among adolescents with nontransfusion‐dependent hemoglobin E/β‐thalassemia and its relationship with anemia severity

Abstract: Background: Low bone mass is common among adolescents with transfusion-dependent -thalassemia despite adequate transfusion and iron chelation. However, there are few reports regarding bone mineral density (BMD) among adolescents with nontransfusion-dependent thalassemia (NTDT). Indeed, only BMD data in patients with nontransfusion-dependent (NTD) -thalassemia intermedia have been reported. No previous study has investigated BMD among adolescents with NTD hemoglobin (Hb) E/ -thalassemia. Objective:To determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…The mechanism of the iron load is likely to be associated with gastro-intestinal (GI) absorption. With increased GI absorption of iron, iron overload occurs late in NTDT patients, leading to a series of complications linked to endocrine disorders including glucose metabolism disorder,4,8 adrenal insufficiency,28 vitamin D deficiency and low bone mass 29,30. It is known that abnormal glucose homeostasis is a fairly common complication of this disease 6.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the iron load is likely to be associated with gastro-intestinal (GI) absorption. With increased GI absorption of iron, iron overload occurs late in NTDT patients, leading to a series of complications linked to endocrine disorders including glucose metabolism disorder,4,8 adrenal insufficiency,28 vitamin D deficiency and low bone mass 29,30. It is known that abnormal glucose homeostasis is a fairly common complication of this disease 6.…”
Section: Discussionmentioning
confidence: 99%
“…We used low bone mass (osteopenia and osteoporosis) for multivariate analysis and found that a higher ferritin (>1000 ng/mL) was significantly associated with low bone mass (RR = 4.6, P = .043) and higher Hb (>9 g/dL) was protective for low bone mass (RR = 0.07, P = .031, data not shown). Low bone mass has a complex nature involving several factors including vitamin D status, calcium intake, levels of osteoclast activity, iron overload, and history of iron chelation . Recently, our group reported that low bone mass can develop as early as prepubertal and pubertal age in NTDT patients, and baseline Hb level was associated with low bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…In measuring the density by Dual-Energy X-ray Absorptiometry each person has three criteria: first index ( Z ): actually indicates Compare between patient׳s bone density and bone density persons are same age and gender. The second index ( T ): the comparison between the patient׳s bone density and bone density persons are same age [5] , [6] , [7] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%